The Effect of Terrorism on International Peace and Security Reasearch Methodolgy - Samadder, Sreeparna (Journal of Advanced Research in Political Science and Governance; Vol 5 No 1 (2021): Journal of Advanced Research in Political Science and Governance, 2021)
Terrorism is a phenomenon that has been known to mankind for more than two millennia, but over this long period of time, no-one has succeeded in defining terrorism in a manner that is universally acceptable and encompasses all essential elements. Therefore, the frequently utilised word ‘terrorism’ does not refer to a well-defined and clearly identified set of factual events or to a widely accepted legal doctrine. The lack of a generic definition cannot invalidate the fact that for several decades, terrorism has been a serious security problem demanding both domestic and international countermeasures. The latter are especially important, as the leading terrorist factions operate internationally in order to gain wider exposure and, as a result, more success, but also to find supporters namely, states that sympathise with their political objectives. The relevant international countermeasures are naturally associated with the Security Council, to whom the states have conferred primary responsibility for the maintenance of international peace and security. The Security Council, a constantly attentive executive organ, has considerable means, of a broad range, at its disposal for that purpose, starting with diplomatic or economic sanctions and ending with military measures. The Security Council was slow in joining the fight against terrorism. The first resolution to use the term ‘terrorism’ was adopted only in December 1985. However, since the end of the Cold War, the body has gradually become more active in this respect and finally assumed a central role after the events of 11 September 2001. By now, the Security Council has on several occasions designated terrorism as a threat to peace. This article aims to understand the essential characteristics of the current definition of threat to international peace and security caused by terrorist act and to understand the problems faced by the Security Council while dealing with terrorism. How to cite this article:  Samadder S. The Effect of Terrorism On International Peace And Security Reasearch Methodolgy. J Adv Res Polit Sci Gov 2021; 5(1): 15-19.